2002
DOI: 10.1542/peds.110.2.e21
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disseminated Encephalomyelitis in Children

Abstract: ABSTRACT. Objective. To describe the epidemiologic, clinical, neuroimaging, and laboratory features; treatment; and outcome in a cohort of children with acute disseminated encephalomyelitis (ADEM).Methods. A 6-year retrospective chart review of children with the diagnosis of ADEM was conducted.Results. Eighteen cases were identified. Sixteen patients (88%) presented in either winter or spring. Thirteen children (72%) had a recent upper respiratory tract illness. Patients presented most often with motor deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
249
9
44

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(319 citation statements)
references
References 21 publications
17
249
9
44
Order By: Relevance
“…The recent investigations showed that 4 (13%) of 31 patients with ADEM had manifestations of ADEM relapses, while 10 (40%) of 25 patients had clinically confirmed multiple sclerosis [21]. As it follows from the data of Schwarz, S., et al's [20] [22], developed multiple sclerosis was found in 14 (35%) of 40 patients in 38-month period of observations (which was confirmed using the Poser criteria). In the Alan investigations, 13 (33.3%) of 39 patients faced the replaces of demyelination disease [9] [21].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The recent investigations showed that 4 (13%) of 31 patients with ADEM had manifestations of ADEM relapses, while 10 (40%) of 25 patients had clinically confirmed multiple sclerosis [21]. As it follows from the data of Schwarz, S., et al's [20] [22], developed multiple sclerosis was found in 14 (35%) of 40 patients in 38-month period of observations (which was confirmed using the Poser criteria). In the Alan investigations, 13 (33.3%) of 39 patients faced the replaces of demyelination disease [9] [21].…”
Section: Introductionmentioning
confidence: 80%
“…The results of observations aimed at the course of this disease for 40 patients with the ADEM diagnosis show that 14 (35%) of them demonstrate developed clinically confirmed multiple sclerosis one year after the primary ADEM episode [20]. Another investigation showed that 5 (23.8%) from 21 patients demonstrated relapses of disseminated encephalomyelitis, and 2 (9.5%) of these 21 patients had multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADEM is more common in winter months and in 80% of childhood cases occurs in the first decade of life (2). The pathogenesis is unclear, but it is thought to be immune-mediated, because in up to threefourths of cases, it follows an antecedent infection or immunization (3). In general, clinical presentation of ADEM may be very heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…In general, clinical presentation of ADEM may be very heterogeneous. However, a combination of altered consciousness or behavior and multifocal neurological deficits, especially in close relation to an infection, should raise clinician's suspicion to consider ADEM in the differential diagnosis (3,4). Some children never have focal neurological signs, whereas in others the initial feature suggests a focal mass lesion (5).…”
Section: Introductionmentioning
confidence: 99%